TINJAUAN OBJEK WISATA AIR TERJUN BAYANG SANI DI DESA KOTO BARU BAYANG KABUPATEN PESISIR SELATAN - Maisarah, Dina; Silfeni, Silfeni; Pasaribu, Pasaribu (Journal of Home Economics and Tourism, 2017)
This research arouse from the observations of researcher towardsBayang Sani waterfall tourist attraction manage by the local people. Thisresearch aims to know the Bayang Sani waterfall tourist attraction in thevillage of Koto Baru Bayang Pesisir Selatan Regency which includes threeterms of attractions: Something to see, Something to do and Something tobuy. This research is a descriptive research with qualitative data. Thetechnique of data collection is done using the method of interview,observation and documentation. Based on the research found a few thingsrelated to Bayang Sani waterfall tourist attractions namely: (a) Somethingto see, views of Bayang Sani waterfall beautiful and cool, there are floraand fauna. (b) Something to do, which can be done in a tourist attractionare bathing, swimming, taking pictures and played Benen attraction whileswimming. (c) Something to buy, kinds of industrial foods, canned drinks,fried foods, a swim pants and facility to shower.Keywords: tourist attraction, something to see, Something to do,something to buy